ANALISIS MANAJEMEN KEUANGAN DESA TERHADAP PEMBANGUNAN DESA (Study kasus Kecamatan Ambalawi kabupaten Bima) - Nurfaidah Nurfaidah; Dwiyani Sudaryanti; Abdul Wahid Mahsuni (e_Jurnal Ilmiah Riset Akuntansi, 2022)
This study aims to determine the management of village financial management on Village Fund Development. This type of research is quantitative research. The population used in this study is the sub-district of Ambalawi, Bima district which consists of the villages of Kole, Rite, Tolowata, Talapiti, Nipa, and Mawu and the sampling technique in this study was purposive sampling with a sample of 42 using simple regression analysis method. From the test results using a regression analysis model, it can be concluded that the variable of village financial management has a significant effect on the development of village funds in villages in Ambalawi sub-district.Keywords: Village financial management and Village Development